2019
DOI: 10.1186/s12889-019-6707-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence and associated factors of mother-to-child transmission of HIV, among children exposed to maternal HIV, in Belgaum district, Karnataka, India

Abstract: Background India lacks data on the incidence of Paediatric HIV. In 2010, the Indian Council of Medical Research commissioned a task force study to estimate the paediatric HIV burden in Belgaum district, Karnataka, India. We estimated the HIV incidence, prevalence and associated risk factors of mother to child transmission of HIV among children exposed to maternal HIV by age 24 months. Methods We included Belgaum resident pregnant women who tested HIV positive between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 23 publications
1
30
1
Order By: Relevance
“…In a study done by Shiradkar et al, 10.29% of seropositive women had an abortion and caesarean section rates declined from 50% to 31% from 2002 to 2011. 6 In a study done by Kwatra Stillbirth rate in our study was 3.23%, compared to 6.9% reported by Radhika et al, and 2% by Potty et al 8,16 There were 96.77% live births in our study as compared to 93.91% in the study done by Kwatra et al, and 93.12% reported by Shiradkar et al 6,7 We reported 100% ART coverage of antenatally registered HIV-positive pregnant women at our institute, 2013 onwards, which surpasses the target of >95% set by the WHO.…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…In a study done by Shiradkar et al, 10.29% of seropositive women had an abortion and caesarean section rates declined from 50% to 31% from 2002 to 2011. 6 In a study done by Kwatra Stillbirth rate in our study was 3.23%, compared to 6.9% reported by Radhika et al, and 2% by Potty et al 8,16 There were 96.77% live births in our study as compared to 93.91% in the study done by Kwatra et al, and 93.12% reported by Shiradkar et al 6,7 We reported 100% ART coverage of antenatally registered HIV-positive pregnant women at our institute, 2013 onwards, which surpasses the target of >95% set by the WHO.…”
Section: Resultscontrasting
confidence: 42%
“…Potty et al, also found that majority of the seropositive women were uneducated housewives. 16 The general trend observed is that most seropositive women are from a low socioeconomic class with a lack of knowledge about HIV, thus widespread education to the masses in a language they understand and using such a method that they will accept and comply to the information given is the need of the hour, such as group counseling with husbands, in-laws and other family members.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these findings demonstrate a relevant peculiarity of the experience of motherhood in the presence of HIV, which can emotionally burden women (13) . Evidence of factors that interfere with VT supports the importance of early identification of HIV-infected pregnant women and their active search for permanent clinical and laboratory evaluation and implementation of prophylactic and support measures (19) . Many pregnant women still fail to perform anti-HIV testing during prenatal care or do not undergo VT prophylaxis, often due to lack of information.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to some other studies, our study did not find an association between either reported maternal ART adherence or VL .1000 copies/mL in the third trimester and neonatal HIV infection. [18][19][20] The limited availability of maternal VL results in this study limits our ability to interpret this finding. However, a study by Garcia et al 21 concluded that although these risk factors can predict transmission, they cannot predict timing of transmission.…”
Section: Discussionmentioning
confidence: 90%